DNA Methylation and Expression of the EgDEF1 Gene and Neighboring Retrotransposons in mantled Somaclonal Variants of Oil Palm - Jaligot, Estelle; Hooi, Wei Yeng; Debladis, Emilie; Richaud, Frédérique; Beulé, Thierry; Collin, Myriam; Agbessi, Mawussé D. T.; Sabot, François; Garsmeur, Olivier; D'Hont, Angélique; Alwee, Sharifah Shahrul Rabiah Syed; Rival, Alain (PloS one, 2014)
The mantled floral phenotype of oil palm (Elaeis guineensis) affects somatic embryogenesis-derived individuals and is morphologically similar to mutants defective in the B-class MADS-box genes. This somaclonal variation has been previously demonstrated to be associated to a significant deficit in genome-wide DNA methylation. In order to elucidate the possible role of DNA methylation in the transcriptional regulation of EgDEF1, the APETALA3 ortholog of oil palm, we studied this epigenetic mark within the gene in parallel with transcript accumulation in both normal and mantled developing inflorescences. We also examined the methylation and expression of two neighboring retrotransposons that might interfere with EgDEF1 regulation. We show that the EgDEF1 gene is essentially unmethylated and that its methylation pattern does not change with the floral phenotype whereas expression is dramatically different, ruling out a direct implication of DNA methylation in the regulation of this gene. Also, we find that both the gypsy element inserted within an intron of the EgDEF1 gene and the copia element located upstream from the promoter are heavily methylated and show little or no expression. Interestingly, we identify a shorter, alternative transcript produced by EgDEF1 and characterize its accumulation with respect to its full-length counterpart. We demonstrate that, depending on the floral phenotype, the respective proportions of these two transcripts change differently during inflorescence development. We discuss the possible phenotypical consequences of this alternative splicing and the new questions it raises in the search for the molecular mechanisms underlying the mantled phenotype in the oil palm.